O dinheiro entre o direito tributário e o direito penal: um estudo sobre a sanção, a coação e a coerção, com o auxílio de Freud - Serafini, Fabricio de Carvalho (2012)
Starting with the forecast, in our positive law, about the extinguishing of the punshability of the tax crimes, for the tax payment (regardless of the time), we arrive at the conclusion that the criminal law is working as collecting agent of the tax law, what it opposes the characteristic of ultima ratio of the first one, characteristic this, pointed since its origins, until the present days, as basic with respect to the same, being one of its differentials for other branches of low. This show us that's more important for our State the payment of the tax then the punishment for who commit tax crimes. This coaction propagated by the accusation for tax crime ended showing very efficient, therefore it increased the tax collection, which will be argued in terms of the general theory of the law, once confirmed what we always defend, unique as characteristic of the complete rules of law, of the several species of norms, that is the forecast of a sanction, for the State, for the one who did not follow the law, imposed in coercitive way. This took us to study the sanction, as well as differentiating the coaction of the coercion, therefore the first one happens before the non compliance of the complete rule of law, threatening the expectation of a sanction, while the second one happens after the non compliance of the complete rule of law, being the application form of the sanction. Confirming our sanctionist idea, we look for the reasons of the fulfilment of many of the rules of law are given by the fear of the sanction, what took us to look for answers in psychology, more specifically in its analysis of the behavior stream (behaviourism), but for our surprise, this showed unfruitful. With this disillusionment, we went to search aid in an opposing chain, the psychoanalysis, more precisely in the ideas of its founder Sigmund Freud. Its ideas in social, cultural and anthropological terms, permeated for its fundamental concepts of the psychoanalysis, had supplied what we looked for, that is, the confirmation of that the human beings follow many norms due to the fear of its sanctions, what it strengthened our sanctionist idea of the law